"He Appeared to Peter": Reconsidering the Hallucination Hypothesis - Smith, Stephen Harry (Neotestamentica, 2019)
In this article, I challenge Wright's view that the bodily resurrection of Jesus provides the "only sufficient and necessary explanation" for the New Testament accounts of the empty tomb and post-resurrection appearances. I then outline Lüdemann's version of the hallucination hypothesis, critique a range of evangelical responses to it, and suggest that part of the reason for the continuing impasse is that neither side engages seriously enough with the psychological and psychiatric literature in the field. My conclusion is that some form of hallucination hypothesis in combination with the concept of collective delusion may be the equal of the evangelical view in terms of its explanatory power.